Why is the highway closed? The unreasonable restriction imposed on the legal services corporation regarding class action suits - Verbic, Francisco (Civil Procedure Review, 2011)
In the paper I discuss the prohibition imposed by the US Congress on the Legal Services Corporation regarding the use of class action suits to provide free legal assistance to the poor. I deal with the creation of the Legal Services Corporation in the US, the scope and advantages of class actions suits (particularly in terms of access to justice), and the role this kind of procedure can play in a context of a deep economic crisis that have deepened the gap in access to the civil justice system. I argue that the aforementioned prohibition to use class actions is unreasonable per se, and that this character is even more remarkable during the current post economic scenario. Therefore, I suggest that the prohibition should be eliminated as soon as possible if there is a real interest in providing free legal services to the poor.